PREVENTION OF OCCUPATIONAL BURNOUT IN MEDICAL WORKERS IN THE CONTEXT OF THE COVID-19 PANDEMIC - Reznikova, Sergeevna; Ganieva, Albina; Verna, Veronica; Yakushev, Aleksandr; Anasenko, Elena (Revista Inclusiones, 2020)
The article addresses the prevention of occupational burnout in medical workers in the conditions of coronavirus infection pandemic development. Due to the increasing frequency of the various manifestations of occupational burnout syndrome symptoms, the lowering average age of medical workers subject to it, and the presence of socially significant consequences of occupational burnout of doctors in the conditions of coronavirus infection pandemic, there is a rising need in further investigation of new effective and safe methods of prevention and correction of adjustment disorders. The objective of addressing the issues of prevention calls for the diagnostic measures for the identification of key characteristics of social and psychological climate in a medical organization. It is confirmed that achieving success in the system of burnout prevention for medical workers is impossible without conscious participation in it. Medical specialists have to become the subjects of their own activity being the active members of the system of occupational burnout prevention.